Strategi Pemasaran Inovatif Untuk Meningkatkan Daya Saing Produk Tahu Dan Tempe Di Pasar Lokal - Fira, Tiara Elma; Monique D S, Eska Prima; Nasution, Suswati; Melinda, Tri Febrina; Indriasari, Nia (LPPM Universitas Dehasen Bengkulu, 2024)
Tofu and tempeh are traditional food products that are very popular in Indonesia. However, in order to remain competitive in the increasingly tight local market, tofu and tempeh producers need to implement innovative marketing strategies. The aim of community service is to identify innovative marketing strategies that can be implemented by tofu and tempeh factory owners, improve the skills of tofu and tempeh factory owners in marketing their products effectively and increase the competitiveness of tofu and tempeh products in the local market through various innovative marketing initiatives. The research method for community service uses in-depth interviews and field observations.